KONTRIBUSI SEKTOR PERIKANAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO DI KABUPATEN BERAU: KONTRIBUSI SEKTOR PERIKANAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO DI KABUPATEN BERAU - Kristian Bondon (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2022)
The purpose of this research is to find out how big the contribution of the fisheries sector is to the Gross Regional Domestic Product in Berau Regency. Based on the results of the research and the results of the contribution data it was concluded that the fisheries sector has a contribution that is still very lacking in contribution to the growth of Gross Regional Domestic Product when viewed with contribution indicators. The contribution of the fisheries sector to Gross Regional Domestic Product in 2015 was 1.08 percent, while in 2016 there was a decrease of 0.01 percent, in 2017 it did not increase or decrease, in 2018 it again did not increase or decrease and in 2019 there was an increase in contribution of 0.01 percent. The largest contribution of the fisheries sector to Gross Regional Domestic Product occurred in 2015 and 2019, namely 1.08 percent. So the hypothesis in this study was rejected.